ANALISIS PENGUASAAN KATAGANTI “MEI”DAN “GE”PADA MAHASISWA ANGKATAN 2017 PENDIDIKAN BAHASA MANDARIN - Annisa Miftahul Khusna; Ina Ina; Bun Yan Khiong (Universitas Tanjungpura, 2019)
AbstractPronoun is important part of Chinese grammar. Pronoun is words with substitution and person. There are many pronouns in Chinese, which is